Laws in Physics. (13th May 2014) - Frisch, Mathias
<x content-type="archive" xml:space="preserve">Abstract</x> This paper critically discusses different philosophical conceptions of laws of nature by examining how putative laws are treated in physical theorizing. These different conceptions are, first, views that take laws to be metaphysically basic; second, Humean views, which take laws to be reducible to patterns of instantiations of non-modal properties; and, third, a cluster of conventionalist or instrumentalist views that understand laws as part of the epistemic toolkit for building models and a reflection of a particular perspective of investigation. I argue that scientific practice best supports a moderate version of the third view: while the laws of physics do not form a single tightly organized axiomatic structure and there exists a multiplicity of frameworks in which putative laws are justified by their predictive use and relevance in a particular context, general overarching principles nevertheless play an important role in physics and provide some integration of different domains.